Perbaikan CCT Pada Multi Machine Infinite Bus Dengan Supercapacitor Energy Storage Menggunakan Critical Trajectory - Talitha Puspita Sari; Rafin Aqsa Izza Mahendra; Ardyono Priyadi; Vita Lystianingrum; Margo Pujiantara; Sjamsjul Anam (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2020)
Transient stability is an important aspect in maintaining the continuity and reliability of the electrical power system when a sudden large disturbance occurs. However, there is a time operation's limitation of the protection system to eliminate disturbance before the system becomes unstable and loses its synchronization. Critical Clearing Time (CCT) is the toleration time to eliminate the fault to keep the system stable. To improve system stability, installing Supercapacitor Energy Storage (SCES) can be one of the methods for extending the CCT values. SCES absorb large amounts of electricity simultaneously when a fault occurs. This paper proposed a determination of SCES' controller effect in extending the CCT. SCES becomes a dummy load and extends the CCT value depending on the controller's ability to respond to a fault. Controller modeling is applied to SCES, which is installed at the bus generator with determined capacity. The modified Fouad and Anderson 9-bus 3-machine system with a single machine to an infinite bus is used to validate the proposed method. Moreover, the critical trajectory method, which is known as a faster calculation and better accuracy than the time domain simulation method, is used to obtain the CCT value. The result shows that the faster controllers work against fault, the higher the CCT value improvement of system CCT. The highest improvement occurs when the controller works at 0.001s.